2014
DOI: 10.1007/s00167-014-3047-9
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb clinical and radiographic osteoarthritis in former elite male athletes

Abstract: In the absence of major bone and soft tissue lower limb trauma during their athletic career, former elite athletes may not be at increased risk of developing clinical OA. Radiographic signs of OA present at a significantly higher incidence and possibly precede the clinical onset of OA. Age, BMI and occupation are identified as strong predictors of the development of OA in former elite athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 37 publications
(44 reference statements)
0
50
0
Order By: Relevance
“…Screening the reference lists of these papers identified a further four studies suitable for inclusion. Therefore, a total of 18 papers were included [ 10 , 11 , 15 30 ].…”
Section: Results: Systematic Reviewmentioning
confidence: 99%
“…Screening the reference lists of these papers identified a further four studies suitable for inclusion. Therefore, a total of 18 papers were included [ 10 , 11 , 15 30 ].…”
Section: Results: Systematic Reviewmentioning
confidence: 99%
“…OA is a prevalent joint disease in the general population, ranging between 10 and 20 % in the male general population (from age 35 and above) in many countries [ 19 , 23 ]. Among former elite athletes from various sport disciplines (ice hockey, basketball, handball, track and field athletes, power sport athletes, weight lifters, shooters and non-impact sport athletes), the prevalence of OA reaches up to 60 % for the hip and ranges from 16 to 95 % for the knee [ 12 , 22 , 23 ]. In our study, 33 % of the former elite athletes reported that a medical professional had diagnosed them with OA (mostly in the lower limbs), which is in accordance with the prevalence found in previous studies [ 9 , 13 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 3 studies, 27,28,31 the prevalence of OA was lower in those with mandatory national military service requirements than in controls; however, the prevalence of OA was significantly lower in only 1 of these studies. 31 Conversely, investigators in 5 studies [27][28][29][30]32 reported a higher prevalence of OA in those with mandatory national military service requirements compared with controls, but again, the prevalence of OA was significantly higher in only 1 of these studies. 30 Authors of 2 studies 37,28 found a higher prevalence for some OA outcomes and a lower prevalence for others.…”
Section: Mandatory National Military Service and Oamentioning
confidence: 98%
“…21 The remaining researchers either examined the incidence or prevalence of OA in active-duty or veteran military populations [22][23][24][25][26] or examined the prevalence of OA in European countries where national military service is mandatory. [27][28][29][30][31][32] Two studies examined OA incidence rates in active-duty military populations 22,23 and compared them with published reference rates in the general population. 3,35,36 No studies were identified that examined OA incidence or prevalence in other tactical athlete populations (eg, law enforcement, first responders).…”
Section: Study Characteristicsmentioning
confidence: 99%